Exploring the Impact of Cd Doping on the Crystal Structure and Electrical Properties of ZnO Using Pymatgen-Based Simulation - Aprilia Dewi Ardiyanti; Tanzilal Mustaqim; Allif Rosyidy Hilmi; Yofinda Eka Setiawan; Aslam Chitami Priawan Siregar (Jurnal Fisika, 2026)
Advances in computing technology are driving the development of advanced materials research. This study aims to model and compare the semiconductor properties of ZnO and ZnO doped with Cd (x=0.5) to form Zn0.5Cd0.5O using a computational approach based on Python Materials Genomics (Pymatgen 3.0) approach within a Python 3.10.18 environment. Modeling was carried out to analyze changes in crystal structure, band gap values, and the correlation between charge carrier concentration and temperature. BSDOS Plotter based on Density Functional Theory (DFT) calculations, was used for energy and Density of States (DOS) graph analysis. The simulation results show that the crystal structure of both materials has a wurtzite lattice shape with angles α = β = 90° and χ = 119°. The band gap value of ZnO is obtained at 3.1 eV, while in Zn0.5Cd0.5O it decreases to 2.7 eV due to the influence of Cd doping which lowers the conduction band energy. The temperature ranges from 500K to 600 K the charge carrier concentration in ZnO increases from 3x10⁵/cm³ to 10⁸/cm³. Meanwhile, the concentrations of electron and hole Zn0.5Cd0.5O increase to 10⁸/cm³ and 7x10⁷/cm.